DUKUNGAN DATABASE DALAM MEMBANGUN WEBSITE DINAMIS YANG INTERAKTIF - Dyah Rhetno Wardhani (LPPM, 2011)
Nowadays, information is an increasing needs for society. According to this needs, it require an information media. One of the media is an easy and quickly accessible website. Website classified in two model namely static and dynamic. Static website only proceed in one way that is merely displaying an information without interaction. On the other hand dynamic website provide interaction with end user. Making a dynamic website require database supporting. Softaware that can be used are Microsoft Access, SQL Server or MySQL depend on database requirement. In order to consistently proceed no matter how many people accessible in the same time need huge database. Furthermore to supporting a dynamic website require programming language like PHP and web editor to simplify designing website page. Key Words: interaction, database, website